An Analitical and Critical Reading on Historicity of the Qur'an in Mohammad Arkoun's Thought | تاريخية القرآن في فكر محمد أركون: قراءة تحليلية نقدية - Fahmi Salim Zubair (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
This article analyzes critically and analytically  M. Arkoun's opinion on the historicity of the Quran, since its revelation until its codification. According to Arkoun, there was an alteration between verbal quran and text that resulted fundamental problems upon the Quran, among them are; mushaf (text book) has been changed, invaha and misinterpreted by the early Muslim ideologist and radical. Arkoun thinks that Musliill now has to review and purify  the quranic discourse from any historicity infiltration, in order to bring back the Quran to its original.